Juan Parra del Riego: a song to the vertiginous nature of the world (Orkopata. Revista de Lingüística, Literatura y Arte, 2025)
This article revisits the life and work of the Peruvian poet Juan Parra del Riego, a key figure for understanding the artistic and social transformations that followed the First World War. From a contemporary perspective, it combines classical readings with recent contributions that shed new light on his literary production. The study addresses his poetic evolution and his transition from modernism to the avant-garde. In addition, it examines the development of innovative metrical structures in his work, as well as the aesthetic dialogue with figures such as Manuel González Prada. His role as a translator is also analyzed, along with his ability to condense, through accelerated images and vertiginous forms, the dynamic and agitated spirit of his time. For all these reasons, the article pays tribute to an author whose work stands as a vibrant testimony to Latin American modernity.
Keywords: literature; Peru; Parra del Riego; poetry; avnat-garde